PERANCANGAN TATA KELOLA TEKNOLOGI INFORMASI - Vina Jamila Kinta Vina (JENTRE, 2020)
Seeking the needs of IT Governance at regional office of the Ministry of religious affair in West Sumatera is the aim of the research. Thus, it creates the design of IT Governance documents fills with the policy related to leadership, structure and processes critical IT’s. This research used research and development method with a COBIT 4.1 (Control Objectives for Information and Related Technology 4.1) framework and its supporting tools. The method of analysis was through semi-structured interview to the head of regional office of the Ministry the religious affair in West Sumatera and any related documents on IT Implementation. The result was in a form of documents on IT governance which has the policy dealt with leadership, structure and  processes critical IT’s at regional office of the Ministry of religious affair in West Sumatera.